PTU-166 Diagnosis of Gastro-Oesophageal Reflux Disease (Gord) by Histology of Mucosal Biopsies from Distal Oesophagus: Agreement with Prolonged PH Monitoring. (4th June 2013) - Sweis, R; Chang, F; Fox, M; Anggiansah, A; Lee, A; Valdes, A; Wong, T
Abstract : Introduction: Prolonged wireless pH-monitoring (Bravo) increases diagnostic yield compared to 24 hr pH-studies. Studies have shown a weak association between oesophageal acid exposure from 24 hr pH-studies and mucosal disease on distal oesophageal histology. This study assessed the association between Bravo, endoscopic findings and distal oesophageal histology. Methods: From July 2009 to August 2010, 63 consecutive patients with typical reflux symptoms had endoscopy with biopsies taken from 3 & 9 o'clock position at and 2cm proximal to the Z-line prior to pH capsule fixation 6cm proximal to the Z-line for prolonged (up to 96 hr) Bravo. All biopsies were assessed by the 6-parameter Zentilin histology score (Zentilin et al Gastroenterol 2005). GORDdiagnosis was based on "Average" acid exposure (Total Reflux; TR > 5.3% time pH < 4) over the time period measured and/or symptom-association (symptom index; SI > 50%) Results: Adequate biopsy samples were available from 57/63 patients (mean age 44 (range 17–78); 27M). 37/57(65%) patients had GORD based on either TR (n = 30) or SI(n = 32). 20/57(35%) were both TR & SI negative (Functional Heartburn; FH). 18 FH patients had no mucosal changes, 2 had grade A oesophagitis. There was no difference in individual histology parameters between GORD vs. FH (p > 0.05) apart from increased 'intra-epithelial neutrophils' (IEN) at the Z-line (9/37 vs. 1/20 positive; p = 0.031) and 2cm proximally (6/37 vs. 0/20 positive; p = 0.012). The combined Zentilin histology score was also higher in GORD at the Z-line (p = 0.079) and 2 cm proximally (p = 0.05). Using GORD diagnosis from 96 hr Bravo as reference, ROC analysis revealed that, although sensitivity remained poor, specificity of GORD diagnosis based on histology improved with IEN and total histology score. With increased IEN, sensitivity was 30% at the Z-line and 20% 2 cm above while specificity was 92.6% at the Z-line and 100% 2cm proximally. For the optimal Zentilin histology score of ≥7, sensitivity was 40.5% at the Z-line and 18.9% 2cm above while specificity was 95% at the Z-line and 100% 2 cm proximally. Histology corroborated GORD diagnosis (based on positive TR) in 11/30 and 20/30 patients at the Z-line and in 6/30 and 11/30 patients 2 cm proximally. Conclusion: Histology lacks sensitivity as a stand-alone diagnostic test; however high IEN or total histology scores have high specificity for GORD diagnosis based on pH-study results. Thus, routine biopsy of the distal oesophagus may be sufficient to diagnose GORD and obviate the need for ambulatory pH-studies in this subgroup of patients. Disclosure of Interest: None Declared.